NTU : DSO Industrial Attachment Report - Ho, Evan Wei Li (2014)
The NTU Undergraduate Satellite Program provides a platform for students to design and develop various subsystems of its satellite projects. An automated solar panel virtual instrumentation system was developed to characterize solar panels and obtain their rated power, voltage and current values. A brief study was done to understand the principles of how solar cell converts light into electrical energy, and how different light intensities and electrical configurations will affect the output of the solar cell. A supporting structure was fabricated to scan for an area which provides an equivalent power of a solar constant, across the light beam of the sun simulator. A LabVIEW program was further improved to implement automation to the system to record IV and power curves of the solar panel at specific temperatures. Calibration of the thermocouple and translation of the output of the LM94022 temperature sensor was done to provide the user 2 temperature references for observation. Delay and finer voltage intervals were parameters added to the Electronic Load to provide more accurate values when performing the testing operation. The system was used to test for electrical characteristics of 2 solar panels, whereby one of the solar panels have a cracked solar cell after going through thermal test. Although the cracked solar did not exhibit a drastic change in electrical properties, the effect of photoluminescence was observed. The next project involves the development of a satellite camera. A case study was done to understand the effects on the image by changing values of the programmable parameters of the camera. A program was written in C to interface with the Opal Kelly FPGA module, which is connected to a camera sensor designed by a research team in NTU. Basic functions such as manual calibration of the camera, loading and saving from a text file, and capturing an image was successfully implemented in the program. To increase the reliability of the camera operation in space conditions, the auto calibration function was added to automatically adjust the reference voltage of the ADC which determines whether a visible image could be captured. In addition, the multiple image capture function was implemented to capture images at different exposure times, such that the optimal calibration setting can be studied and recorded on the ground station. A setup of a testing system for the line scan mode function was also proposed, however it is not tested due to the damage on the rotary stage after over running the piezo electric motors.